The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jts.22451
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Physical and Psychological Symptoms and Traumatic Military Deployment Exposures

Abstract: Current paradigms regarding the effects of traumatic exposures on military personnel do not consider physical symptoms unrelated to injury or illness as independent outcomes of trauma exposure, characteristically dealing with these symptoms as comorbidities of psychological disorders. Our objective was to ascertain the proportions of deployed military personnel who experienced predominantly physical symptoms, predominantly psychological symptoms, and comorbidity of the two and to examine the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Cognitively, individuals who have experienced trauma are often tormented by thoughts that reflect intensely negative core beliefs about themselves, which can include, ‘I will never be able to feel normal emotions again,’ ‘I feel like an object, not like a person,’ ‘I do not know myself anymore,’ or, ‘I have permanently changed for the worse’ (Cox, Resnick, & Kilpatrick, 2014 ; Foa, Tolin, Ehlers, Clark, & Orsillo, 1999 ). Somatically, recent research points increasingly towards the notion that trauma can leave a lasting physical representation, where lower back pain, general muscle aches and pains, flatulence/burping, or feeling as though your bowel movement has not finished have been identified as somatic disturbances that significantly perturb the sense of self (Graham, Searle, Van Hooff, Lawrence-Wood, & McFarlane, 2019 ). Here, Graham et al ( 2019 ) found that two thirds of cases of military-related posttraumatic stress disorder (PTSD) are missed when a PTSD checklist for the Diagnostic and Statistical Manual (DSM-5; APA, 2013 ) (i.e.…”
Section: The Sense Of Self In the Aftermath Of Traumamentioning
confidence: 99%
“…Cognitively, individuals who have experienced trauma are often tormented by thoughts that reflect intensely negative core beliefs about themselves, which can include, ‘I will never be able to feel normal emotions again,’ ‘I feel like an object, not like a person,’ ‘I do not know myself anymore,’ or, ‘I have permanently changed for the worse’ (Cox, Resnick, & Kilpatrick, 2014 ; Foa, Tolin, Ehlers, Clark, & Orsillo, 1999 ). Somatically, recent research points increasingly towards the notion that trauma can leave a lasting physical representation, where lower back pain, general muscle aches and pains, flatulence/burping, or feeling as though your bowel movement has not finished have been identified as somatic disturbances that significantly perturb the sense of self (Graham, Searle, Van Hooff, Lawrence-Wood, & McFarlane, 2019 ). Here, Graham et al ( 2019 ) found that two thirds of cases of military-related posttraumatic stress disorder (PTSD) are missed when a PTSD checklist for the Diagnostic and Statistical Manual (DSM-5; APA, 2013 ) (i.e.…”
Section: The Sense Of Self In the Aftermath Of Traumamentioning
confidence: 99%
“…Participants were asked to indicate the severity of symptoms over the past month on a 4-point scale selecting never, mild, moderate, or severe. Each symptom was further dichotomized as "no" ("never") or "yes" ("mild", "moderate," or "severe"), as per previous military studies (40)(41)(42). We assigned physical distress caseness as endorsing 16 or more physical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies on PTSD in Lebanon are limited to few studies with small samples pertaining to specific groups (not the general population). While previous literature has widely documented the relations between trauma characteristics (number and type of trauma) and the incidence and symptomology of PTSD (Jakob et al, 2017;Janoff-Bulman, 1989;Graham et al, 2019), studies recently has been moving from studying the effects of trauma characteristics on PTSD towards investigating how trauma is assimilated in one's identity (trauma centrality) and its effects on PTSD (Bernard et al, 2015;Brensten & Rubin, 2006, 2007Robinaugh & McNally, 2011). Bernard et al (2015) also documented that trauma centrality has a wider influence on PTSD than the mere characteristics of the traumatic event.…”
Section: Rationalementioning
confidence: 99%
“…The exposure to a potentially traumatic event such as sexual assault, car accident, combat and so serves as the gatekeeper for the diagnosis and is presumed to be the root cause of the symptoms. Accordingly, research has focused primarily on studies that showed association between trauma characteristics (number of traumas and type of trauma) and the incidence and symptomology of PTSD (Jakob et al, 2017;Janoff-Bulman, 1989;Graham et al, 2019). Studies have indicated that a higher number of traumatic experiences is more likely to lead to severe PTSD symptoms, with interpersonal traumata, such as sexual abuse, being particularly predictive (Jakob et al, 2017;Janoff--Bulman, 1989;Graham et al, 2019;Lancaster et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation